2018
DOI: 10.1161/circimaging.117.006973
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Coronary Angiography–Derived Plaque Characteristics Predict Major Adverse Cardiovascular Events

Abstract: These data demonstrate that HRP is most likely an independent predictor of MACE, which supports the inclusion of HRP reporting in clinical practice. However, at this point, it remains unclear whether HRP reporting has clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 34 publications
2
65
3
2
Order By: Relevance
“…Taking into account that LV, LL, VV, TPV, CPV and NCPV show the composition of plaques rather than their hemodynamic relevance the missing correlation to iFR® is as expected. Plaque composition is most likely an independent predictor of MACE as shown in a meta-analysis by Nerlekar et al [24]. Especially non-calcified plaque showed the strongest association in this study.…”
Section: Tablesupporting
confidence: 71%
“…Taking into account that LV, LL, VV, TPV, CPV and NCPV show the composition of plaques rather than their hemodynamic relevance the missing correlation to iFR® is as expected. Plaque composition is most likely an independent predictor of MACE as shown in a meta-analysis by Nerlekar et al [24]. Especially non-calcified plaque showed the strongest association in this study.…”
Section: Tablesupporting
confidence: 71%
“…In fact, besides luminal area stenosis, other coronary plaque morphology and composition parameters may affect downstream myocardial perfusion. Accordingly, lesion-specific morphological features such as positive remodeling and noncalcified plaque volume have been associated with detrimental downstream hyperemic myocardial perfusion and FFR, independent of lesion severity, and are strong predictors of major cardiovascular events [ 112 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Conversely, spotty calcification on CT is associated with[ 2-fold increase risk in plaque rupture (HR 2.25; 95% CI 1.26-4.04; P = 0.006). 16 Similarly, analysis of plaque vulnerability by intravascular ultrasound has revealed that patients with stable angina have fewer and larger contiguous plaques compared to those who present with acute coronary syndrome, who have a greater number of small calcium deposits. 17 Taken together, these findings suggest that calcification may have a biphasic effect on plaque stability with early spotty deposition increasing plaque vulnerability and denser calcium deposition that group together into large areas stabilizing plaque ( Figure 1).…”
Section: Imaging More Than the Cac Volumementioning
confidence: 99%